PENGABDIAN KEPADA MASYARAKAT DI DESA PADAULUN UNTUK MENINGKATKAN SIKAP PEDULI LINGKUNGAN BIJAK DALAM MENGELOLA SAMPAH DAN HIJAUKAN MASA DEPAN - Rola Manjaleni S.E.,M.Si Linda; Aiva Tyanka F; Devita Nurwulan; Fahmi Ilham; Fiqri Cahya M; Siti Linda M; Sephia; Syifa Azkia M; Tika Permata A; Tri Handoyo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The increasing volume of household waste, low public awareness of waste sorting and management, and the decreasing availability of green open spaces have become environmental issues faced by the residents of Padaulun Village, Majalaya District, Bandung Regency. These conditions encouraged the implementation of a Community Service Program aimed at improving public knowledge and awareness of environmentally friendly waste management, promoting the habit of sorting waste from an early stage, and increasing concern for environmental greening. The activities carried out included waste management socialization for the community and the planting of 26 mahogany tree seedlings as a greening initiative. Overall, the program had a positive impact on enhancing environmental awareness through the successful implementation of educational activities on environmental stewardship and tree-planting efforts to support greening in Padaulun Village.